Beyond memory : an anthology of contemporary Arab American creative nonfiction - Kaldas, Pauline; Mattawa, Khaled (The University of Arkansas Press, 2020)
"This anthology brings together the voices of both new and established Arab American writers, creating a compilation of essays and creative nonfiction that reveal the stories of the Arab diaspora. Writers from Egypt, Lebanon, Libya, Palestine, and Syria explore issues related to politics, culture, and racism. Coming from different countries and religions and including first and second-generation immigrants as well as those whose identities encompass more than a single culture, these writers tell stories that speak to the complexity of the Arab American experience. They travel through time and geography to reveal the circular nature of identity, inviting the reader to enter into an ever evolving landscape. Ranging from the traditional to the experimental, these essays present narratives in innovative styles. At this point in our history, such stories are urgently needed, and this anthology gives greater insight into the lives of Arab Americans. Entering into these personal stories allows readers to engage with the complexity of the Arab American community. The varied experiences of being an Arab American emerges through these pages with astounding vision"--